Optimization of Integrated Waste Management in Kamal Village, West Pemulutan District : Penelitian - Selma Kemuning Aquinta; Alya Syafitri Lubis; Rahmat Hidayat; Yoga Jusri Pratama; Dea Natalia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Waste management remains a challenge in many villages, including Kamal Village, which still relies on incineration and river disposal. This study aims to analyze the state of waste management, identify structural, institutional, and social factors that weaken the role of village government, and formulate an integrated optimization strategy. The method used is descriptive qualitative through observation, interviews with village officials, the community, and the Environmental Agency, and documentation studies. The results indicate that management is suboptimal due to the absence of village regulations, limited facilities and budget, weak official capacity, lack of coordination, and low public awareness and participation. Optimization strategies include policy advocacy, capacity building, and the implementation of Appropriate Technology (TTG) such as the preparation of Village Regulations, the establishment of Task Forces and Waste Banks, environmental education, and the use of composters and fly larvae cultivation. It is concluded that synergy between village government, the community, and stakeholders is key to realizing an effective, participatory, and sustainable integrated waste management system.